2021
DOI: 10.3390/obesities1030015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Adherence to the 24-Hour Movement Guidelines and Overweight and Obesity among Children in Northeastern Japan: A Longitudinal Study before and during the COVID-19 Pandemic

Abstract: There are few studies comparing adherence to Canadian 24-hour Movement Guidelines (24-h MG) before and during the COVID-19 pandemic and exploring the pandemic’s effect on childhood obesity. This survey-based 2-year study investigated changes in obesity and adherence to the 24-h MG in children before and during the COVID-19 pandemic. Data were collected at two points in time: pre-COVID-19 (May 2019; T1; n = 247) and during-COVID-19 (May 2021; T2; n = 171). Participants were healthy elementary school children ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“… 2 Preliminary evidence indicated that PA levels declined and screen time increased among Japanese school-aged children during the pandemic (2021) as compared to before the pandemic (2019). 4 , 5 Additionally, recent reviews summarizing the international evidence from the first year of COVID-19 found that lockdown restrictions led to reduced PA, increased screen time, and altered sleep patterns, with a shift to later bed and wake times among children and adolescents. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“… 2 Preliminary evidence indicated that PA levels declined and screen time increased among Japanese school-aged children during the pandemic (2021) as compared to before the pandemic (2019). 4 , 5 Additionally, recent reviews summarizing the international evidence from the first year of COVID-19 found that lockdown restrictions led to reduced PA, increased screen time, and altered sleep patterns, with a shift to later bed and wake times among children and adolescents. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…Regarding obesity‐related indicators, the most common obesity‐related indicators were zBMI [35, 37, 38, 40, 42, 44–47, 49, 55, 56], waist circumference [36, 38, 45, 48, 53, 54, 60], BMI [35, 36, 39, 41, 48, 53, 58], body fat by bioelectrical impedance analysis [57, 62] or dual‐energy x‐ray absorptiometry [38, 55], only obesity [48, 63], and overweight/obesity [35, 37, 41, 43, 46, 50–52, 56, 59, 61–63]. Regarding the measurement of the 24‐hour movement recommendations, physical activity was assessed by accelerometer‐based measures in 17 studies [35, 37, 38, 40, 41, 43, 45, 46, 49, 51–56, 58, 59] and self‐reported measures by young people and parents in 12 studies [36, 39, 42, 44, 47, 48, 50, 57, 60–63]. Screen time was self‐reported by young people in 14 studies [36, 38, 39, 44, 46–48, 50, 54, 56–58, 61, 62] and by parents in 15 studies [35, 37, 40–43, 45, 49, 51–53, 55, 59, 60, 63].…”
Section: Resultsmentioning
confidence: 99%
“…Screen time was self‐reported by young people in 14 studies [36, 38, 39, 44, 46–48, 50, 54, 56–58, 61, 62] and by parents in 15 studies [35, 37, 40–43, 45, 49, 51–53, 55, 59, 60, 63]. Sleep duration was determined by accelerometer‐based measures in 9 studies and self‐reported measures by young people and parents in 20 studies [35, 36, 40, 42–45, 47–53, 57, 59–63]. Finally, 15 studies compared meeting all three recommendations with meeting any of the recommendations (i.e., not meeting all three) [35, 37, 40, 42–45, 47, 49, 50, 53–56, 59], whereas 14 studies compared meeting all three recommendations with meeting none of the recommendations [36, 38, 39, 41, 46, 48, 51, 52, 57, 58, 60–63].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the 24-h MG (e.g., high PA, low screen time, adequate sleep) contribute to preschool children’s physical, psychological, and mental health as they develop a stronger immune system [ 3 , 6 , 7 ]. Nevertheless, many children across the globe do not engage in adequate amounts of moderate-intensity to vigorous-intensity PA (MVPA) [ 8 , 9 ], spend much of their time on screen-viewing [ 10 , 11 ], and sleep late at night or for short durations [ 12 , 13 ]. Such behaviors have been noted to have an adverse impact on the physical and mental health of children [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%